Transparency of materiality analysis in GRI‐based sustainability reports. (26th October 2020) - Machado, Bianca Alves Almeida; Dias, Lívia Cristina Pinto; Fonseca, Alberto
Abstract: While materiality analysis is often regarded as essential to sustainability reporting, there is a shortage of empirical studies about its transparency in published reports. This study had a three‐fold objective: (a) identify stakeholders and respective techniques of engagement in the materiality analysis; (b) quantify disclosures of materiality‐related indicators; and (c) explore the influence of assurance, standard, and headquarters' location in the transparency of materiality analysis. Based on a quantitative content analysis of 140 GRI‐based sustainability reports, this study found that, overall, organizations did not disclose comprehensive and detailed information about their approaches to identifying material topics. About 22% of the evaluated indicators were not fully disclosed in the sample. Non‐parametric tests suggested that third‐party assurance, type of GRI standard, and location of headquarters are unlikely to affect the rates of transparency. The study calls for further standardization and methodological development of materiality analysis in sustainability reporting.